Theoretical Aspects of Insurance for International Banks of Development - Y. A. Akhvlediany (Plekhanov Russian University of Economics, 2018)
The article shows the importance of insurance for international banks of development in order to resolve social and economic problems of regional economy. The authors analyze figures of insurance markets of member-states of the Eurasian Economic Union and identify the acute lines of development of regional banks. They put forward recommendations on theoretical basis of insurance for international banks of development, risk-management in the Eurasian Bank of Development and introduction of advanced insurance technologies. The role of insurance market and the banking sector in shaping the common finance market of member-states of the Eurasian Economic Union was shown. On the basis of analyzing the macro-economic standing of insurance markets in the EAEU the level of their development was identified. It was proposed to organize common reinsurance capacities on the EAEU territory, which could provide transparent and regulated conditions of reinsurance space of EAEU member-states functioning, extend the access to reinsurance, develop regional markets of member-states and remove barriers hindering integration of insurance markets of EAEU partners. The authors come to the conclusion about the importance of developing tools of the regional system of insurance protection in regional banks' work in conditions of EAEU infrastructure development. Through analyzing the volume of premiums and the amount of assets it was shown that Russian insurance market is the most developed market on the Eurasian territory and the insurance potential of banks depends on regional peculiarities and provision of advanced insurance technologies.